Effect of Temperature and Film Thickness on Residual Stress and Texture of ${\rm Re}_{2}{\rm O}_{3}$ Buffer Layers for YBCO Coated Conductor - Arda, L.; Ataoglu, S.; Bulut, O. (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Re2O3 (Re = Er, Gd, Ho, Y and Yb) was prepared by sol-gel synthesis using metal-organic precursors. Residual stress and microstructure in the Re2O3 buffer layers were investigated as a function of temperature and film thickness. Textured Re2O3 buffer layers were grown on biaxially textured-Ni (100) substrates using chemical solution deposition. Films were annealed at 1150degC under a flowing 4% H2-Ar gas. X-ray diffraction of the buffers showed strong out-of-plane orientation on Ni tape. Residual stress in various thicknesses of buffer layers was calculated. The surface morphologies and microstructure of all samples were characterized using SEM and AFM.